Logic, Dilemma and Realization of Digital Transformation of Classroom Teaching Assessment - LIN Ying; TIAN Yingqian; WANG Jinrong (Jiaoshi jiaoyu xuebao)
The potential of digital technology highlights its advantages in real-time monitoring, data mining, data analysis and data processing of classroom teaching assessment, which can significantly improve the objectivity, accuracy and completeness of the assessment. In the context of the digital age, clarifying the theoretical and technological basis for the integration of classroom teaching assessment and digital technology can help deepen the understanding of the digital transformation of the assessment. The dilemma lies in the insufficient digital literacy of the subjects, the constraints of algorithmic black box on assessment methods, lack of standards for assessment contents, and ethical misconduct in feedback data. Based on this, the digital transformation of classroom teaching assessment should be realized through: firstly, improving the digital literacy of assessment subjects and adhering to the origin of educating; secondly, strengthening multidimensional data collection and dynamic digital algorithms; thirdly, reshaping the content of embodied assessment to build a diverse and integrated assessment method; fourthly, regulate technology usages and improve data supervision and management systems.